Paraspinal muscles activities in S-shaped adolescent idiopathic scoliosis during physiotherapeutic scoliosis specific exercise: a case–control study - Yu Wang; Shuhan Wang; Minghui Gu; Jiang Xu; Xiaolin Huang; Lingfeng Xie (BMC Musculoskeletal Disorders, 2025)
Abstract Background While Insights into the dynamics of the paraspinal muscles can contribute to more targeted interventions for individuals with adolescent idiopathic scoliosis (AIS), few studies have focused on changes in the paraspinal muscles of AIS during Physiotherapeutic Scoliosis-Specific Exercise (PSSE). Therefore, this study compared the differences in muscle activities between AIS and healthy subjects during PSSE, aiming to provide a scientific guidance of clinical treatment and daily life for AIS. Methods Twelve S-shaped AIS and ten age-matched healthy controls participated. Five paired target paraspinal muscle groups (upper end vertebra, apex vertebra, lower end vertebra of the thoracic and apex vertebra, lower end vertebra of the lumbar) were assessed by surface electromyography (sEMG) during five postures: relaxed sitting, erect sitting, symmetrical pole-sitting correction and asymmetrical pole-sitting over-correction (1 and 2). Hold each posture for 20s and repeat 3 times to obtain sEMG data. Results The results revealed that exercises effectively activated paraspinal muscles in AIS subjects, with a stronger activation observed during asymmetrical exercises (P < 0.05). Compared to healthy group, AIS subjects exhibited inhibited paraspinal muscle activity during relaxed sitting at the apex vertebra of thoracic and lumbar spine (P < 0.01). Additionally, in erect sitting, AIS subjects also showed inhibition of the paraspinal muscles at the apex of thoracic spine (P < 0.05). Furthermore, erect sitting failed to enhance symmetric muscle activation in S-shaped AIS. Conclusions These findings indicate that increasing the proportion and intensity of asymmetric exercises in PSSE treatments could enhance the activation and functional recovery of paraspinal muscles in AIS individuals. Furthermore, close monitoring of paraspinal muscle activity during rehabilitation is recommended to enable timely adjustments to the treatment regimen. Trial registration Chinese Clinical Trial Registry ChiCTR2300075167, 28th of August, 2023.